The Implementation of INA-CBGs (Indonesia Case-Based Groups) System and Strategic Response in Institutional Theory Perspective (Case Research in RSUD Dr. Saiful Anwar Malang) - Clarias, Citrus; Sukoharsono, Eko G; Mulawarman, Aji D (Universitas Negeri Malang, 2018)
This research aimed to understand the implementation of INA-CBGs system and organization response in the institutional perspective at RSUD Dr. Saiful Anwar (RSSA). To achieve these objectives, a descriptive qualitative method was used with case study as a strategy. The implementationof INA-CBGs system was analyzed using the institutional forces that exist in the institutional theory of Dimaggio& Powell (1983), and analysis of an organizations response wasbased onstrategic responses ofinstitutional forces by Oliver (1991). The results showed that coercive pressures in the implementation of the INA-CBGs system derived from government regulations.Source normative pressure came from the education and professional standards. Source mimetic pressures came from competition with other hospitals andthe uncertainty of the health industry environment. The strategic response in facingcoercive pressure wasgiving a passive approval and performsomestrategic innovation. While the normative pressurewas responded by training and a more selective recruitment process. Last response related to mimetic pressurewasby imitating theexisting practice from other hospitals.